Hot Seat Change Shift Using Boarding Gate at PT Putra Perkasa Abadi Site Borneo Indobara - Margono*, Margono; Prayitno, Koko; G.M, Ryaldo Rivelino; Riyanto, Endik; Islamudin, Rozzaq Alhanif (Universitas Syiah Kuala, 2023)
PT. Putra Perkasa Abadi is one of the coal mining contractors in the IUP (Mining Business License) area of PT. Borneo Indobara. With the increasing production targets for overburden and coal getting, one of the key performance indicators to determine the optimal performance of mechanical equipment in coal mining is monitoring the UA value during mining activities. Data shows that the delay change shift activity affects a production loss of 2 hours. To maximize working hours, it is necessary to improve the delay during operating standby change shift. This effort involves the Hot Seat Change Shift method using a Boarding Gate in the Change Shift Area. This has reduced the figure to 0.65 hours or increased by 6% from the initial UA.